CEREAL GRAIN DRYING BED JET CONVENTIONAL - Condorhuamán C., Cesario (2004)
It has been obtained the mass and heat transfer coefficients from experimental data of the granular- cereals drying such as rice, wheat, barley and oat in a conventional spouted bed column. The range of mass air flow varies from 5.2 and 40 kg/sm2. The mass transfer coefficients varies from 0.331 and 0.789 Kg/(sm2atm), and heat transfer coefficient varies from 43.7 and 53.8 W/m2K